Mniejszości narodowe w Polsce – zarys historyczno-prawny - Kundera, Weronika (Studia Prawa Publicznego, 2019)
Poland has a centuries long tradition of being a tolerant country, manifested as well by the symbolic offi cial name: Poland of Both Nations (1569–1795). Poles, Lithuanians and numerous national minorities lived side by side in the territory of the Polish Republic and today their descendants are Polish citizens. During the time of partitions Poles maintained strong national community feelings, which subsequently helped in the building of the Second Polish Republic. The reborn Poland was again a multi-national state, however, certain nationalistic feelings started to emerge. After World War II as a result of the extermination of minorities and mass resettlements, the historical multinational character disappeared and the minimal set of rights granted to minorities in the Constitution of 1952 had led to their ethnic exclusion. After March 1968, the rights of minorities had become drastically limited. This continued till the Third Republic of Poland when the policy of the Communist authorities promoting the building of Poland for the Poles had been abandoned and the new government pursued to preserve and protect national and ethnic minorities. Today, members of minorities have the same rights as ethnic Poles, and their rights are guaranteed in the Constitution of 1997 and other legislative acts including the most important one, i.e. the Act on National and Ethnic Minorities and the Regional Language of 2015, which deﬁ nes national and ethnic minorities and determines the competences of the State bodies in the area of enforcing minorities rights. These solutions have secured Poland an opinion of a model state when it comes to the protection of minorities rights. There are nine national minorities ofﬁ cially recognised in Poland. Each has a diff erent situation resulting from historical conditions, circumstances, national stereotypes, relationship with the States of their origin and the position of the Polish minority in this State. Two main problems which minorities in Poland are facing today is their shrinking populations and threats to their culture from the Polish and global cultures. Immigration might be a possible remedy but low economic attractiveness of Poland fails to attract new immigrants which means that in the future Poland may practically become a one-nation state.